Dimension of mobile information behaviour / Zuraidah Arif...[et al.] - Arif, Zuraidah; Abdul Rahman, Abd Latif; Mohammed Ghazali, Asmadi; Mohd Ghazali, Muhammad Faizal Iylia (Universiti Teknologi MARA, Kedah, 2017)
Mobile information is a significant access point for human information activities. Theories and models of human information behaviour have been developed over several decades but have not yet considered the role of the user’s computing device in digital information interactions. This paper reviews the literature that leads to developing a dimension of mobile information behaviour. Based on the literature review, information needs, information access, information retrieval and information use are recognized as the dimensions of mobile information behaviour. The study is significant to understand the nature of user behaviour in searching, retrieving and using of information via the mobile device.